We claim that the eigenvalues of "A^{-1}" are "\\frac{1}{2},-1,-\\frac{1}{3}" . We will prove that in 2 steps :
"\\frac{1}{\\lambda} v_\\lambda = \\frac{1}{\\lambda} id \\cdot v_\\lambda = \\frac{1}{\\lambda} A^{-1}Av_\\lambda = \\lambda \\cdot \\frac{1}{\\lambda}(A^{-1}v_\\lambda) = A^{-1} v_\\lambda"
So "v_\\lambda" is an eigenvector of "A^{-1}" associated to an eigenvalue "\\frac{1}{\\lambda}" .
"A(v_\\alpha)=A (\\frac{1}{\\alpha}A^{-1}v_\\alpha) = \\frac{1}{\\alpha} (A A^{-1}v_\\alpha) = \\frac{1}{\\alpha} v_\\alpha"
So we have that "\\frac{1}{\\alpha}" is an eigenvalue of "A" .
Thus we have proven that eigenvalues of "A^{-1}" are "\\frac{1}{2}, -1, -\\frac{1}{3}" and there is no other eigenvalues.
Comments
Leave a comment